Characteristics candlenut shell-based activated Carbon for reduction Iron (Fe) in surface water from Bratasena Tulang Bawang, Lampung - Elisa, Elisa; Shintawati, Shintawati; Afifah, Dian Ayu; Ramandani, Adityas Agung (Journal of Natural Sciences and Mathematics Research, 2024)
Candlenut shells are only used as fuel, and some are thrown away, so their use has not been maximized. Because of their high carbon content, candlenut shells may be used to create adsorbents. This study looks at how different activator concentrations of KOH activators can be used to make adsorbents from candlenut shells. The study will investigate how various activator concentrations affect the ability of adsorbents based on candlenut shells to bind molecules. Furthermore, the investigation will examine the possible uses of these adsorbents in diverse sectors, including air purification and wastewater treatment. This research was carried out using the Completely Randomized Design (CRD) method, which consisted of 1 activator KOH concentration of 0.5 M, 1 M, 1.5 M, 2 M, and 2.5 M with 3 replications each. The finding demonstrated that adsorbent products activated with 0.5 M KOH yield the highest quality and satisfied SNI 06-3770-1995 requirements for an ash and water content of 10.21% and 0.98%, respectively. The adsorbent product has an iodine absorption capacity of approximately 639.39 mg/g, comparable to SNI 06-3770-1995. For iron metal, the adsorbent product exhibits an adsorption capacity and absorption efficiency of 0.14 mg/g and 98.30%, respectively. The Freundlich adsorption isotherm model is suitable for this investigation, with a Kf value of 0.14 mg/g and an R2 of 0.9999.